Facile synthesis of ternary MnO2/graphene nanosheets/carbon nanotubes composites with high rate capability for supercapacitor applications. (20th August 2015) - Ramezani, M.; Fathi, M.; Mahboubi, F.
Highlights: MnO2 /GNS/CNT composite is synthesized through a facile chemical method. The composite electrode shows the highest specific capacitance of 367 F g −1 . Specific capacitance of MnO2 /GNS/CNT is about 6.58 times that of the pure MnO2 . This composite electrode shows the best rate capability among all MnO2 composites. Graphical abstract: Abstract: Ternary composites of manganese dioxide/graphene nanosheets/carbon nanotubes (MnO2 /GNS/CNTs) have been fabricated through a facile chemical method involving in situ growth of MnO2 particles on the surface of graphene oxide (GO)/CNT hybrid following by the chemical reduction of GO. The morphology and structure of the resulting materials are characterized using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), ultraviolet/visible (UV/Vis) spectroscopy and X-ray diffraction (XRD). The supercapacitive behaviors of the sample electrodes are evaluated by cyclic voltammetry (CV), galvanostatic charge/discharge and electrochemical impedance spectroscopy (EIS) techniques in 1 M Na2 SO4 aqueous solution. The electrochemical measurements show that the specific capacitance of MnO2 /GNS/CNT composite at the scan rate of 20 mV s −1 (367 F g −1 ) is much higher than that of pure MnO2 (55.7 F g −1 ), binary MnO2 /CNT (180 F g −1 ) and MnO2 /GNS (310 F g −1 ) composites. In addition, the MnO2 /GNS/CNT composite shows excellent rate capability, with 79.3% capacitance retention after a 5-fold increase in potential scan rate and better cycling stability, with 83% capacitance retention after 3000 cycles. These advances can be attributed to the synergistic effects of GNS and CNT in the composite structure, which facilitates electrolyte ions accessibility to the electrode material during electrochemical process as well as maintaining the mechanical strength.